Antibiotic susceptibility and antibacterial activity of neutralized cell-free supernatant of Lactobacillus rhamnosus MT539286 against Foodborne and Clinical pathogens. - Hasan, Muffrah; Arif , Afsheen; Hasnain , Abid; Abbas, Tanveer (International Journal of Endorsing Health Science Research, 2020)
Background: The emergence of horizontally transferable antibiotic resistance (AR) in probiotic strains of lactic acid bacteria (LAB) has incited a need to establish stringent safety measures for the assessment of commercial probiotics. Lactobacillus rhamnosus is not only a prevalent constituent of commercially available probiotics but also has an abundant presence in fermented foods. Methodology: The present study tested antimicrobial activity and antibiotic susceptibility of L. rhamnosus isolated from fermented cabbage. Agar well diffusion assay was used to determine the antibacterial activity against a number of Gram-positive and Gram-negative bacteria, and antibiotic susceptibility testing was used to determine the antibiogram of several antibiotics. For this, the neutralized Cell-Free Supernatant (nCFS) of L. rhamnosus was used, which exhibited antibacterial activity against several bacteria. Results: Antagonistic activity of nCFS of L. rhamnosus was found against Listeria monocytogenes, Bacillus cereus, Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa, Vibrio parahaemolyticus, Salmonella typhimurium, Klebsiella pneumoniae, Salmonella enterica. Maximum inhibitory activity was observed against Listeria monocytogenes. Whereas, no activity was found against Staphylococcus epidermidis, Streptococcus pyogenes, Bacillus subtilis, Vibrio alginolyticus, Proteus mirabilis and Proteus vulgaris. The intensity of inhibition among the isolates was in the sequence of Listeria monocytogenes > Escherichia coli > Bacillus cereus > Vibrio parahaemolyticus > Salmonella typhimurium. L. rhamnosus was found susceptible against Chloramphenicol and Novobiocin. Moreover, it exhibited resistance to Amoxicillin, Levofloxacin, Oxacillin, Streptomycin and Tobramycin. Conclusion: In conclusion, this study suggests that the use of L. rhamnosus as a probiotic requires extensive examination of AR genes present in this strain.